Uji Aktivitas Antibakteri Ekstrak Metanol dan Fraksi Daun Kenikir (Cosmos caudatus Kunth) terhadap Salmonella typhi - Achmad Syarifudin Noor; Bawon Triatmoko; Nuri Nuri (Pustaka Kesehatan, 2020)
The leaves of kenikir are known to have many benefits, one of which can be used as medicine. Kenikir leaves are reported to have antibacterial activity against the bacteria Salmonella typhi (S.typhi). S. typhi is a bacterium that causes typhoid fever. Typhoid fever is still an endemic disease in Asian countries, especially Indonesia. Typhoid fever became the third largest disease in Indonesia in 2010. The study related to the antibacterial activity of kenikir leaf fraction to S. typhi has never been reported. Therefore, it is necessary to conduct research related to the antibacterial activity of extracts and leaf fractions of kenikir to compare their potential against S. typhi. The study was conducted using the disk diffusion method using 5 series of concentrations namely 5%, 10%, 15%, 20%, and 30%. Tests were carried out on methanol extract, hexane, ethyl acetate, and methanol-water fraction. The results showed that highest inhibition zone diameter is 7,75 mm which is reached by methanol extract. The order of the highest inhibiting zone diameter are extract, hexane, ethyl acetate, and methanol-water fraction.